Sprouty2 loss‐induced IL6 drives castration‐resistant prostate cancer through scavenger receptor B1. Issue 4 (14th March 2018) - Patel, Rachana; Fleming, Janis; Mui, Ernest; Loveridge, Carolyn; Repiscak, Peter; Blomme, Arnaud; Harle, Victoria; Salji, Mark; Ahmad, Imran; Teo, Katy; Hamdy, Freddie C; Hedley, Ann; et al.
Abstract: Metastatic castration‐resistant prostate cancer (mCRPC) is a lethal form of treatment‐resistant prostate cancer and poses significant therapeutic challenges. Deregulated receptor tyrosine kinase (RTK) signalling mediated by loss of tumour suppressor Sprouty2 (SPRY2) is associated with treatment resistance. Using pre‐clinical human and murine mCRPC models, we show that SPRY2 deficiency leads to an androgen self‐sufficient form of CRPC. Mechanistically, HER2‐IL6 signalling axis enhances the expression of androgen biosynthetic enzyme HSD3B1 and increases SRB1‐mediated cholesterol uptake in SPRY2‐deficient tumours. Systemically, IL6 elevated the levels of circulating cholesterol by inducing host adipose lipolysis and hepatic cholesterol biosynthesis. SPRY2‐deficient CRPC is dependent on cholesterol bioavailability and SRB1‐mediated tumoral cholesterol uptake for androgen biosynthesis. Importantly, treatment with ITX5061, a clinically safe SRB1 antagonist, decreased treatment resistance. Our results indicate that cholesterol transport blockade may be effective against SPRY2‐deficient CRPC. Synopsis: Tumour‐induced IL6 modulates host lipid metabolism to drive treatment‐resistant castration‐resistant prostate cancer (CRPC). Blocking tumoral cholesterol uptake using SRB1 antagonist or restoring systemic cholesterol homeostasis using statins decreases treatment resistance. SPRY2 deficiency drives androgen self‐sufficient form CRPC though HER2‐mediated IL6. IL6 mediates tumoural androgen synthesis by inducing HSD3B1 expression. Systemic IL6 mediates host adipose lipolysis and stimulates hepatic cholesterol biosynthesis leading to elevated levels of circulating cholesterol. SPRY2 loss‐induced IL6 mediates tumoural cholesterol uptake through the HDL receptor SRB1 to drive CRPC. Using a clinically safe SRB1 antagonist (ITX5061) decreased treatment‐resistance. Abstract : Tumour‐induced IL6 modulates host lipid metabolism to drive treatment‐resistant castration‐resistant prostate cancer (CRPC). Blocking tumoral cholesterol uptake using SRB1 antagonist or restoring systemic cholesterol homeostasis using statins decreases treatment resistance.